The effects of varying in incubation time and temperature of methyl salicylate as a clearing agent on the quality of breast tissue slides - Fariha Fathiasari; Wiwin Wiryanti; Adang Durachim; Mamat Rahmat (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2024)
Non-polar clearing agents have the ability to dissolve breast adipose tissue. While fat dissolution occurs during the clearing process, careful monitoring of adipose cell membranes mis crucial due to their impact on the behavior of breast cancer cells and disease progression. Xylol is a widely employed clearing agent. However, its toxicity and prolonged clearing time necessitate the exploration of alternatives. In this context, methyl salicylate emerges as a viable substitute. It is non-polar nature facilitates efficient fat dissolution, leading to quicker tissues clarification. This study adopted a quasi-experimental method, utilizing 24 pieces of breast tissue as the sample. These tissue sample were divided into six groups according to the treatment regimen. The treatment groups involved breast tissue clearing using xylol for 2x60 minutes at room temperature, methyl salicylate for 2x30 minutes at room temperature, and methyl salicylate at 60°C for 20 minutes, 30 minutes, 2x20 minutes, and 2x30 minutes. The quality of breast tissue slides was assessed by analyzing the color contrast between the nucleus and cytoplasm using ImageJ software, along with the clarity of adipose cell cell membrane using microscopy. The results indicated that prolonged exposure at high temperature resulted in poor quality breast tissue slides. Conversely, tissue clearing with methyl salicylate for 2x30 minutes at room temperature exhibited excellent contrast between the nucleus and cytoplasm, as well as clear adipose cell membranes. Further study is warranted to explore the applicability of methyl salicylate as a clearing agent in tissues with lower fat content.